Japanese capitalism since 1945 : (M.E. Sharpe, 1989)
Contents: This book introduces students of the Japanese economy to a broad range of critical contemporary Marxian analyses by Japanese economists. Each of the five essays - on economic policy, agriculture, big business, labour relations, and foreign trade and investment - is written by a specialist in the field. The introduction places the essays in the wider context of contrasting theories of Japanese economic development. While such writings constitute an important part of the economic literature in Japan, virtually none of the great body of Marxian writing on Japanese capitalism has heretofore been available in English.